PHARMACOKINETIC INVESTIGATION OF REMOGLIFLOZIN IN RAT PLASMA SAMPLES BY HIGH-THROUGHPUT HPLC-MS-MS - INTURI, RAVIKANTH; RAJU, MEDEPALLI DAVID; BASAVESWARA RAO, MANDAVA VENKATA; INTURI, SRIKANTH (International Journal of Applied Pharmaceutics, 2022)
Objective: Remogliflozin (REMO), a selective inhibitor of the renal sodium-dependent glucose transporter 2 channel, which could increase urine glucose excretion and lower plasma glucose in humans. To establish a simple, sensitive and completely validated HPLC-MS-MS approach for the analysis of Remogliflozin in rat plasma samples. Methods: The method was developed after simple step protein precipitation by acetonitrile and Empagliflozin (EMPA) was used as internal standard. Separation was done on an CORTECS C18, 90 Å, 2.7 µm, 4.6 mm X 150 mm with an isocratic mobile phase consisting of 0.1% Formic acid: acetonitrile (20:80%, v/v) and pumped at a flow stream of 0.8 ml/min at ambient temperature. Results: The approach developed showed fine calibration curve in the quantity range of 5-1000 pg/ml with correlation coefficient (r2) of ≥ 0.9997 and the intra-run accuracy and precision was 99.91 to 109.07% and 0.17 to 1.34, inter-run accuracy and precision was 99.8 to 101.54 and 0.17 to 1.66 according to FDA guidelines. Conclusion: The newly designed and validated approach was simple, fast and applied effectively for single-dose oral pharmacokinetic investigation in Wistar male rats for the quantification of REMO in biological matrix.